GC–MS and LC-TOF–MS profiles, toxicity, and macrophage-dependent in vitro anti-osteoporosis activity of Prunus africana (Hook f.) Kalkman Bark - Richard Komakech; Ki-Shuk Shim; Nam-Hui Yim; Jun Ho Song; Sungyu Yang; Goya Choi; Jun Lee; Yong-goo Kim; Francis Omujal; Denis Okello; Moses Solomon Agwaya; Grace Nambatya Kyeyune; et al. (Scientific Reports, 2022)
Abstract Osteoporosis affects millions of people worldwide. As such, this study assessed the macrophage-dependent in vitro anti-osteoporosis, phytochemical profile and hepatotoxicity effects in zebrafish larvae of the stem bark extracts of P. africana. Mouse bone marrow macrophages (BMM) cells were plated in 96-well plates and treated with P. africana methanolic bark extracts at concentrations of 0, 6.25, 12.5, 25, and 50 µg/ml for 24 h. The osteoclast tartrate-resistant acid phosphatase (TRAP) activity and cell viability were measured. Lipopolysaccharides (LPS) induced Nitrite (NO) and interleukin-6 (IL-6) production inhibitory effects of P. africana bark extracts (Methanolic, 150 µg/ml) and β-sitosterol (100 µM) were conducted using RAW 264.7 cells. Additionally, inhibition of IL-1β secretion and TRAP activity were determined for chlorogenic acid, catechin, naringenin and β-sitosterol. For toxicity study, zebrafish larvae were exposed to different concentrations of 25, 50, 100, and 200 µg/ml P. africana methanolic, ethanolic and water bark extracts. Dimethyl sulfoxide (0.05%) was used as a negative control and tamoxifen (5 µM) and dexamethasone (40 µM or 80 µM) were positive controls. The methanolic P. africana extracts significantly inhibited (p < 0.001) TRAP activity at all concentrations and at 12.5 and 25 µg/ml, the extract exhibited significant (p < 0.05) BMM cell viability. NO production was significantly inhibited (all p < 0.0001) by the sample. IL-6 secretion was significantly inhibited by P. africana methanolic extract (p < 0.0001) and β-sitosterol (p < 0.0001) and further, chlorogenic acid and naringenin remarkably inhibited IL-1β production. The P. africana methanolic extract significantly inhibited RANKL-induced TRAP activity. The phytochemical study of P. africana stem bark revealed a number of chemical compounds with anti-osteoporosis activity. There was no observed hepatocyte apoptosis in the liver of zebrafish larvae. In conclusion, the stem bark of P. africana is non-toxic to the liver and its inhibition of TRAP activity makes it an important source for future anti-osteoporosis drug development.